Ratiometric fluorescence assay for butyrylcholinesterase activity based on a hemicyanine and its application in biological imaging. (January 2022) - Wan, Chenyang; Li, Jiajia; Gao, Jian; Liu, Haihong; Zhang, Qian; Zhang, Peng; Ding, Caifeng
Abstract: Butyrylcholinesterase (BChE) is an esterase expressed by the liver, which is released into the plasma immediately. The activity of BChE in the serum is a sensitive indicator for determining the protein synthesis function of liver cells. Therefore, the development of high-efficiency chemical tools for detecting BChE is in urgent need. In this work, based on the ingenious combination of specific BChE enzymatic reaction, a ratiometric fluorescence probe was established to easily achieve the determination of BChE with high sensitivity with LOD calculated as low as 0.077 μg/mL. This probe also possesses a superior selectivity to BChE without the interference of other biological species even acetylcholinesterase (AChE), which gives it great potential to work for sensing in biological samples. The accurate IC50 (0.195 mM) of iso-OMPA, a specific inhibitor of BChE, could also be examined, indicating the excellent performance in elucidating inhibitory efficacy. In addition, the probe can be used for fluorescence imaging of BChE activity in living cells as well as animal tissues. These advantages indicate that the probe has important practical value for the monitoring of BChE activity. Graphical abstract: Image 1 Highlights: A ratiometric fluorescent probe W1 for the determination of BChE was constructed. The probe provides high sensitivity for BChE with a LOD calculated as 0.077 μg/mL. W1 possessed a superior selectivity to BChE without interference of other species. The accurate IC50 of iso-OMPA also indicated the excellent sensing performance. The sensing scheme is workable in biological samples including serum and cells.